Meiotic chromosomal studies in family Zygophyllaceae R. Br. from Rajasthan - Gupta, Raghbir Chand; Kaur, Kuljit; Singh, Vijay (The Indian Journal of Genetics and Plant Breeding, 2016)
Present paper deals with the cytomorphological study of 4 genera and 5 species belonging to family Zygophyllaceae collected from various localities of Rajasthan. Three cytomorphovariants of Tribulus terrestris have been observed with 2n=24, 36 and 48. Peganum harmala with 2n=12 (based on x=6) is reported for the first time from world level, earlier the species is based on x=12. The presence of B-chromosomes also makes the first report of the species from world level. Fagonia cretica (2n=22), Tribulus alatus (2n=24) and Zygophyllum simplex (2n=16) have been cytologically worked out for the first time from India.